Financial Statement Analysis and Investors’ Decision: Empirical evidence from listed petroleum firms in Nigeria - Jabar, Adebola Abass; Osunkunle, Usman Adesola; Akomolafe , Busola Adesola (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
This research focuses on the effect of financial statement analysis on investors’ decisions regarding listed petroleum firms in Nigeria. The methodology employed was a regression based approach using panel data covering a period of ten years which was obtained from financial statements oflisted petroleum firms in Nigeria. The result showed significant relationship between equity and fmancial performance indices adopted for the study. Petroleum firms owe a duty to fully disclose matters concerning their operations so as to aid investors in making investment decisions because investment decision-makers rely on information obtained from financial statements to predict future rates of return. Without the financial statement, there will be a problem of how to determine the profit and performance of a company. We discovered from the analysis that profitability is not the major factor for making decisions but it plays a vital role in making good investment decisions by existing or prospective investors. Conclusion was drawn based on the findings that financial statement plays a vital role in investment decision-making while recommending that no investment decision should be taken without the consideration of a company’s financial statements.